Aging impairs protective host defenses against Clostridioides (Clostridium) difficile infection in mice by suppressing neutrophil and IL-22 mediated immunity. (December 2018) - Peniche, Alex G.; Spinler, Jennifer K.; Boonma, Prapaporn; Savidge, Tor C.; Dann, Sara M.
Abstract: Background: Morbidity and mortality associated with Clostridioides (formerly Clostridium ) difficile infection (CDI) rises progressively with advanced age (≥65 years) due in part to perturbations of the gut microbiota and immune dysfunction. Epidemiological data of community-acquired CDI suggests increased susceptibility may begin earlier during middle-age (45–64 years) but the causation remains unknown. Methods: Middle-aged (12–14 months) and young (2–4 months) adult mice were infected with C. difficile, and disease severity, gut microbiome and innate immune response were compared. Cytokine reconstitution studies were performed in infected middle-aged mice. Results: Infection of middle-aged mice with C. difficile led to greater disease compared to young controls, which was associated with increases in C. difficile burden and toxin titers, and elevated bacterial translocation. With the exception of an expansion of C. difficile in middle-aged mice, microbiome analysis revealed no age-related differences. In contrast, middle-aged mice displayed a significant defect in neutrophil recruitment to the colon, with diminished levels of innate immune cytokines IL-6, IL-23 and IL-22. Importantly, recombinant IL-22 administration during CDI reduced morbidity and prevented death in middle-aged mice. Conclusion: Increased susceptibility to C. difficile occurs in middle-aged mice modeling the community-acquired CDI demographics and is driven by an impaired innate immune response. Highlights: Middle-aged mice exhibit increased susceptibility to Clostridium difficile infection. Susceptibility was associated with an impaired innate immune response. Levels of IL-22 were significantly lower in middle-age mice. Administration of IL-22 during infection reduced age-related morbidity and mortality.